Reconstruction of osseous defect with symphysis block graft for implant placement - John Roshan; L.K. Surej Kumar; Sherin N. Rahim; G.A. Adersh; Mathew Joseph Thuruthel; Ahammed Haris H (Journal of Oral Biology and Craniofacial Research)
Introduction: Symphysis being an autogenous bone graft serves as one of the best graft for augmenting osseous defects of alveolar process with excellent results. It has been favoured mainly due to its local availability, accessibility and lesser resorption compared to other bones in the region. Case report: A 21/M reported to the department of Implantology with the complaint of missing tooth in the upper front tooth region since 1 year. History revealed extraction of upper left central incisor an year ago following trauma. Diagnosis was made as Siebert's Class I with horizontal bone loss irt 21 region with a bone defect of 10.54 x 5.08 x 4.85 mm. So a complete prosthetic rehabilitation protocol was made with an implant placement and grafting was planned with symphysis being most favourable. Conclusion: The mandibular symphysis is a reliable intraoral graft site that can be used in the office setting with low morbidity. Because of the intraoral approach and lack of cutaneous scarring, patient acceptance is high.